Determination of fetal heart rate short‐term variation from umbilical artery Doppler waveforms. (3rd December 2020) - Cahill, L. S.; Stortz, G.; Ravi Chandran, A.; Milligan, N.; Shinar, S.; Whitehead, C. L.; Hobson, S. R.; Millard, S.; Macgowan, C. K.; Kingdom, J. C.; Sled, J. G.; Baschat, A. A.
ABSTRACT: Objective: To evaluate the feasibility of using umbilical artery (UA) Doppler waveforms to measure fetal heart rate (FHR) short‐term variation (STV) across gestation. Methods: This was a prospective longitudinal study, conducted at two study sites, of 195 pregnancies considered low risk. Pulsed‐wave Doppler of the UAs was performed at 4‐weekly intervals, between 14 and 40 weeks of gestation, using a standardized imaging protocol. Up to 12 consecutive UA Doppler waveforms were analyzed using offline processing software. FHR STV was calculated using average R–R intervals extracted from the waveforms and baseline corrected for FHR. Results: Baseline‐corrected FHR STV increased significantly with gestational age (conditional R 2  = 0.37; P  < 0.0001) and was correlated inversely with FHR (conditional R 2  = 0.54; P  < 0.0001). The STV ranged (median (interquartile range)) from 3.5 (2.9–4.1) ms at 14–20 weeks' gestation to 6.3 (4.8–7.7) ms at 34–40 weeks' gestation. The change in heart rate STV did not differ between study sites or individual sonographers. Conclusions: UA Doppler waveforms offer a robust and feasible method to derive STV of the FHR. It should be emphasized that the UA Doppler‐derived STV is not interchangeable with measurements derived with computerized cardiotocography. Accordingly, further investigations are needed to validate associations with outcome, in order to determine the value of concurrent fetal cardiovascular and heart rate evaluations that are possible with the technique described here. © 2020 International Society of Ultrasound in Obstetrics and Gynecology